2023
DOI: 10.3389/fpsyg.2023.1217877
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of residential environment on residents’ place attachment, satisfaction, WOM, and pro-environmental behavior: evidence from the Korean housing industry

Abstract: This study considers seven residential environment elements and examines their effect on residents’ place attachment (place dependence and place identity), satisfaction, word-of-mouth behavior, and pro-environmental behavior. The study also examines whether gender moderates the proposed relationships. The data were collected from 603 respondents who owned a condominium in Seoul, South Korea. We analyzed the data using structural equation modeling with SmartPLS 4. The finding shows that all seven elements of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…In an interesting study in Korea, ref. [43] found that results differed by gender, as those who identified as female placed a high emphasis on the social environments compared to their counterparts who considered green spaces to have a greater influence on place identity. In Spain, ref.…”
Section: Place Attachment In Residential Satisfactionmentioning
confidence: 96%
“…In an interesting study in Korea, ref. [43] found that results differed by gender, as those who identified as female placed a high emphasis on the social environments compared to their counterparts who considered green spaces to have a greater influence on place identity. In Spain, ref.…”
Section: Place Attachment In Residential Satisfactionmentioning
confidence: 96%
“…Studies indicate that affective attachment to a place significantly inspires nature-protective and pro-eco-friendly behaviors [48]. More precisely, affective attachment to nature and heritage destinations improves a resident's empathy toward and sense of connection to it, encouraging green behaviors [40]. However, studies have rarely integrated affective attachment with other attachment dimensions to explore its effect on residents' pro-environmental green behaviors.…”
Section: Hypothesis 1b (H1b) Place Identity Positively Affects Touris...mentioning
confidence: 99%
“…Research on community attachment has been established in the literature within several domains, including environmental studies, education, green behavior, psychology, management, and tourism (e.g., [36][37][38]), and significant methodological and theoretical progress has been made by scholars in this area [36]. Several scholars have found a significant link between place attachment and pro-environmental green behaviors (e.g., [37,39,40]). Green behavior can be defined as practices by people that foster or engender the sustainable consumption of destination resources [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…A positive relationship or tie between an individual and a specific location is known as a place attachment, which has its roots in attachment theory (Williams and Vaske 2003, p. 831). Many scholars have distinguished between place dependency and place identity (Hosany et al 2017;Maricchiolo et al 2021;Son et al 2023;Wan et al 2022) and have typically thought of place attachment as a multifaceted concept (Martins et al 2022). The recognition of place identity and place dependence as the psychological consequences of place attachment serves as the common thread connecting these disparate scholars' points of view (Wan et al 2022).…”
Section: Place Attachment and Its Antecedents And Descendantsmentioning
confidence: 99%